Actin polymerization-dependent activation of Cas-L promotes immunological synapse stability - Santos, L; Blair, D; Kumari, S; Cammer, M; Iskratsch, T; Herbin, O; Alexandropoulos, K; Dustin, M; Sheetz, M (Nature Publishing Group, 2016)
The immunological synapse formed between a T‐cell and an antigen‐presenting cell is important for cell–cell communication during T‐cell‐mediated immune responses. Immunological synapse formation begins with stimulation of the T‐cell receptor (TCR). TCR microclusters are assembled and transported to the center of the immunological synapse in an actin polymerization‐dependent process. However, the physical link between TCR and actin remains elusive. Here we show that lymphocyte‐specific Crk‐associated substrate (Cas‐L), a member of a force sensing protein family, is required for transport of TCR microclusters and for establishing synapse stability. We found that Cas‐L is phosphorylated at TCR microclusters in an actin polymerization‐dependent fashion. Furthermore, Cas‐L participates in a positive feedback loop leading to amplification of Ca2+ signaling, inside–out integrin activation, and actomyosin contraction. We propose a new role for Cas‐L in T‐cell activation as a mechanical transducer linking TCR microclusters to the underlying actin network and coordinating multiple actin‐dependent structures in the immunological synapse. Our studies highlight the importance of mechanotransduction processes in T‐cell‐mediated immune responses.